2018
DOI: 10.1111/nuf.12253
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of workplace bullying on nursing competences among registered nurses in Jordanian public hospitals

Abstract: To prohibit bullying behavior, nurse administrators have to construct a work environment that demonstrates respect and fairness and which is transmitted through nurses' communication pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
3
30
1
Order By: Relevance
“…Initially, a total of six studies (totalling 2,434 participants) that presented the NAQ‐R results as the sum of the Likert Scale item scores were included in the first meta‐analysis: Al‐Sagarat et al (2018), Cengiz, Demirbag, and Yiıldizlar (2018), Obeidat, Qan’ir, and Turaani (2018), Fang, Huang, and Fang (2016), Oh et al (2016b), Hickson, (2013). The Hickson (2013) study for the purpose of this investigation has been divided into two separate analyses for Magnet and Non‐Magnet Group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, a total of six studies (totalling 2,434 participants) that presented the NAQ‐R results as the sum of the Likert Scale item scores were included in the first meta‐analysis: Al‐Sagarat et al (2018), Cengiz, Demirbag, and Yiıldizlar (2018), Obeidat, Qan’ir, and Turaani (2018), Fang, Huang, and Fang (2016), Oh et al (2016b), Hickson, (2013). The Hickson (2013) study for the purpose of this investigation has been divided into two separate analyses for Magnet and Non‐Magnet Group.…”
Section: Resultsmentioning
confidence: 99%
“…The weekly working hours of nurses should, therefore, be carefully managed. Higher competence (Al‐Sagarat et al, 2018; Obeidat et al, 2018) was identified as one of the most significant predictors of decreased workplace bullying. Therefore, improving nurses’ competence may be an effective intervention for reducing bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, nursing managers and administrators should emphasize the professionalism needed in the workplace and actively support said professionalism. Further, workplace violence is related to job competency, and nurses with low competency are more susceptible to workplace violence (AL‐Sagarat, Qan'ir, AL‐Azzam, Obeidat, & Khalifeh, 2018; Berry et al, 2016). Therefore, newly graduated nurses may be a target for focused violence.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO estimates that the global needs-based shortage of nurses and midwives will be over 9 million by 2030 3. An unhealthy work environment, including workplace bullying, has been reported as a reason that nurses leave the profession 3–6. Workplace bullying was first identified in the 1980s by the Swedish researcher Leymann, who defined it as an ongoing conflict in which the victim is subjected to one or more negative acts weekly over a period of at least 6 months 7.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported that unit specification plays a role 23 26 27. Nurses indicate that their main bullying sources are their managers/supervisor6 13 23 or nursing peers 28. In addition, this phenomenon is influenced by cultural factors and world region,29 30 which is why to create optimal intervention in bullying, studies must be conducted across countries 16…”
Section: Introductionmentioning
confidence: 99%